(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Digital Leadership is a must-have skill for any scholar student. This study provides scholar students insight into how to view digital leadership as an avoidable situation. Digital leadership can be embedded into the mind of scholar students through the development of their information technology skills and knowledge. A quantitative method with percentages for all items calculated is used in this research. 100 students that are participating in field practice in 2021 from Universitas Pendidikan Indonesia were taken as the respondents. The methodical structure of the instrument is; 1) open questions, and 2) closed questions with two options. The result of this study concludes that digital leadership requires the following; 1)(a) Foreign language, (b) Writing skills, (c) Problem Solving skills, (d) Computer skills, (e) Public Speaking comprehensiveness, (f) Team Work, (g) Time Management, and (h) Communication, and 2) An average 95% respondent said, they are activists both outside and inside the campus, leaders in campus organizations, know and can operate information telecommunication tools, able to learn to operate information technology tools, take benefit from their skills, facilitate decision making, exercise authority, carry out work, exercise leadership, establish human relations, strengthen brotherhood, and establish cooperation, have adequate information technology equipment, an environment that allows the use of information technology in work, the organization has implemented digitalization, has played a role in digitizing the organization, has played a role in digitalization transformation within the organization, faced challenges in digital transformation within the organization, there are challenges that come from within their organization, challenges that come from outside their organization, challenges that come in the form of financing and mindset, and for limitations with collaboration.